2019
DOI: 10.1080/10942912.2019.1650762
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cholesterol triterpenoid acids from Saurauia vulcani Korth. (Actinidiaceae)

Abstract: Two triterpenoid compounds, 3β-hydroxy-Olean-12-en-28-oic acid (1) and 3,19-Dihydroxyurs-12-en-28-oic acid (2) were isolated from the leaves of Saurauia vulcani Korth. (Actinidiaceae). The chemical structures of compounds 1-2 were elucidated with spectroscopic data (UV, IR, 1 H, 13 C, DEPT 135º, HMQC, HMBC, 1 H-1 H COSY NMR) and MS as well as compared with previously reported spectra data. All the compounds were evaluated for their anti-cholesterol activity by the Liebermann-Burchard (LB) colorimetric assay. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Several other triterpenoid compounds have been reported to have anticholesterol properties. The triterpenoid compounds, 3β-hydroxyolean-12-en-28-at acid and 3,19-dihydroxy-urs-12-en-28-at acid found in the Saurauia vulcani Korth, showed anticholesterol activity [15]. Kedaung (Parkia timoriana (DC) Merr) was also found to contain two phytosterol compounds, β-sitosterol and campesterol, which can reduce total blood cholesterol and LDL levels 30-50% by inhibiting cholesterol absorption in the intestinal lumen [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other triterpenoid compounds have been reported to have anticholesterol properties. The triterpenoid compounds, 3β-hydroxyolean-12-en-28-at acid and 3,19-dihydroxy-urs-12-en-28-at acid found in the Saurauia vulcani Korth, showed anticholesterol activity [15]. Kedaung (Parkia timoriana (DC) Merr) was also found to contain two phytosterol compounds, β-sitosterol and campesterol, which can reduce total blood cholesterol and LDL levels 30-50% by inhibiting cholesterol absorption in the intestinal lumen [25].…”
Section: Resultsmentioning
confidence: 99%
“…The anticholesterol activity of the compounds was determined using photometry. Cholesterol reacts with the Liebermann-Burchard reagent [15]. Simvastatin was used as a positive control.…”
Section: Anticholesterol Activitymentioning
confidence: 99%
“…In a study involving the potential of triterpenoid compounds to lower cholesterol, Bachmid et al, 41 found that an ethanol extract of patikan leaves containing triterpenoid compounds had anti-cholesterol efficacy at doses of 30 mg/kg BW, resulting in a 71 percent reduction in cholesterol levels. Musa et al, 23 reported two triterpenoid compounds from Saurauia vulcani Korth, which demonstrated an exceptional anti-cholesterol activity. The anti-cholesterol properties of this compound are influenced by the presence of hydroxyl groups, double bonds, and carboxylic acid.…”
Section: Anti-cholesterol Activity Test Resultsmentioning
confidence: 99%
“…The anti-cholesterol activity of ethanol and methanol extracts, as well as each fraction (n-hexane, ethyl acetate, and methanol), was determined using the photometric method where cholesterol is reacted with the Liebermann-Burchard reagent. 22,23 Simvastatin was used as a positive control. The concentrations of the extracts used were 50, 100, 200, 300, 400, and 500 μg/mL, while the concentrations of the simvastatin used were 10, 20, 30, 40, 50, 75, and 100 μg/mL.…”
Section: Anti-cholesterol Activity Testmentioning
confidence: 99%
“…plant were collected in Silangkitang Village, North Tapanuli, North Sumatera Province, Indonesia. 34 They found two triterpenoid compounds as anti-cholesterol agent, 3β-hydroxy-Olean-12-en-28-oic acid (1) and 3,19-Dihydroxyurs-12-en-28-oic acid (2). The chemical structure of compounds 1 and 2 was shown in Figure 2.…”
Section: Chemical Compoundsmentioning
confidence: 98%